MODEL DAN STRATEGI PENGEMBANGAN UMKM INDUSTRI KREATIF UNGGULAN BERBASIS POTENSI LOKAL DI KOTA JAMBI - Faradilla Herlin; Hasan Basri (Journal Development, 2018)
Studies and studies are needed to map and identify business units of superior creative industry SMEs to be developed in the city of Jambi. The problem in research is which creative industry-based SMEs have the potential to be developed and how can the development model of creative industry SMEs be based on local potential and finally how is the formulation of policy strategies in the development of superior creative industries based on local potential in Jambi City. On the basis of the results of the analysis that has been carried out, it can be concluded that the following are the first, local potential creative industries based on SMEs that have the advantage to be developed in Jambi City are handicraft industries, design industries, fashion industries, film, video and photography industries, game industries interactive, publishing and printing industries, and the television and radio industries. Second, the development model of creative industry-based SMEs based on local potential must pay attention to efforts to increase the creativity of the workforce both through formal education, training and through wage levels, which will have a positive impact on the development of creative industry MSMEs. Likewise, efforts to increase investment, manager's ability and increase production creativity.